THE EFFECT OF REGIONAL TAX, REGIONAL RETRIBUTION AND BALANCING FUND ON CAPITAL EXPENDITURE DISTRICT GOVERNMENTS IN PROVINCE SUMATRA UTARA - M Firza Alpi (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study is to determine and analyze the effect of Regional Taxes on Capital Expenditures on District Governments in Sumatera utaraProvince for the period 2015-2019, to determine and analyze the effect of Regional Levies on Capital Expenditures on District Governments in Sumatera utara Province for the period 2015-2019, to determine and to analyze the influence of Regional Levies on Capital Expenditures on District Governments in Sumatera utaraProvince for the period 2015-2019 and to determine and analyze the effects of Regional Taxes, Regional Levies, and Balanced Funds on Capital Expenditures on District Governments in Sumatera utaraProvince for the period 2015-2019. The results showed that there was an influence between Local Taxes on Capital Expenditures in District Governments in Sumatera utaraProvince for the 2015-2019 Period. There is an influence between Regional Levies on Capital Expenditures in District Governments in Sumatera utara Province for the 2015-2019 Period. There is an influence between Balanced Funds on Capital Expenditures in District Governments in Sumatera utaraProvince for the 2015-2019 Period. There is the influence of Local Taxes, Regional Levies and Balanced Funds on Capital Expenditures in District Governments in Sumatera utaraProvince for the 2015-2019 Period. The result of the R-Square value is known to be worth 40.9%, meaning that it shows that around 24% of the Capital Expenditure variable (Y) is influenced by Local Taxes, Regional Levies and Balancing Funds. The remaining 59.1% of returns on assets are influenced by other variables not examined in this study.Keywords: Local Taxes, Regional Levies, Balancing Funds, Capital Expenditures